A large, refractory nosocomial outbreak of Klebsiella pneumoniae carbapenemase (KPC)-producing Escherichia coli demonstrates carbapenemase gene outbreaks involving sink sites require novel approaches to infection control - Decraene, V; Phan, H; George, R; Wyllie, D; Akinremi, O; Aiken, Z; Cleary, P; Dodgson, A; Pankhurst, L; Crook, D; Lenney, C; Walker, A; et al. (American Society for Microbiology, 2018)
Carbapenem-resistant Enterobacteriaceae (CRE) are a health threat, but effective control interventions remain unclear. Hospital wastewater sites are increasingly highlighted as important potential reservoirs. We investigated a large Klebsiella pneumoniae carbapenemase (KPC)-producing E. coli (KPC-EC) outbreak and wider CRE incidence trends over eight years in the Central Manchester Foundation NHS Trust (CMFT), UK, to determine the impact of Infection Prevention and Control measures. Bacteriology and patient administration data (2009 to 2017) were linked; a subset of CMFT/regional KPC-EC isolates (n=268) was sequenced. Control interventions followed international guidelines and included cohorting, rectal screening (n=184,539 screens), environmental sampling, enhanced cleaning, and ward closure/plumbing replacement. Segmented regression of time trends of CRE detections was used to evaluate the impact of interventions on CRE incidence. Genomic analysis (n=268 isolates) identified spread of a KPC-EC outbreak clone (ST216, strain-A; n=125) amongst patients and the environment, particularly on two cardiac wards (W3/W4), despite control measures. ST216 strain-A had caused an antecedent outbreak, and shared its KPC plasmids with other E. coli lineages and Enterobacteriaceae. CRE acquisition incidence declined after W3/W4 closure and plumbing replacement, suggesting an environmental contribution. However, W3/W4 wastewater sites were rapidly re-colonised with CRE and patient CRE acquisitions recurred, albeit at lower rates. Patient relocation and plumbing replacement were associated with control of a clonal KPC-EC outbreak; however, environmental contamination with CRE and patient CRE acquisitions recurred rapidly following this intervention. The large numbers of cases and persistence of blaKPC in E. coli, including pathogenic lineages, is a concern.